Heat Transfer Analysis of Graphene Reinforced PCM for Thermal Energy Storage. Issue 1 (April 2021) - Kumar, Pramod; Singh, Pradeep Kumar; Nagar, Sumit
Abstract: In this experiment, the charging rate of PCM is compared in the summer and winter seasons, while PCM does not charge effectively in winter season due to lower atmospheric temperature but such effects are not seen in summer season. The key objective of this analysis is to increase the thermal efficiency and charging rate by using different nano material concentrations (COOH) varying from 0.25 volume % to 0.75 volume %. This work also includes testing of thermal conductivity, density, specific heat and Nano fluid properties at varying functionalized graphene (COOH) concentrations and temperatures at the heat tranfer fluid (HTF) inlet. Paraffin wax is implemented as a PCM in this process and carboxylic group (COOH) based graphene is the nano material used. The present research's outcome is that the PCM charging time decreases with increasing carboxylic (COOH) graphene concentration in terms of volume percentage. The charging time decreases with the mixing of carboxylic group (COOH) graphene concentration in this experiment in the winter season. The charging rate increases with graphene concentration, as opposed to without the nanomaterial PCM. In this experiment, In the short period of the process time, the significant volume of energy can be retained as charging period is decreased by 25% to 60% by the implementation the carboxylic group(COOH) based nano powder in PCM.